B2C eCommerce strategy and market structure : the survey based approach - Peter Paul Sint; Stefan W. Schmitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper follows two objectives: (i) It demonstrates the merits of the survey based approach to B2C eCommerce characteristics and company strategy, and (ii) it presents empirical evidence of the crucial importance of size and marketing investment in B2C eCommerce markets. It presents econometric estimates of the effects of company characteristics and company strategies on the performance of Viennese B2C eCommerce companies in 2001. We provide econometric analysis of three dependent variables in turn: (i) number of B2C eCommerce customers in 2000, (ii) number of B2C eCommerce employees in January 2001 and (iii) revenue growth rate in 2001. The models do explain the data quite well: Size as well as endogenous sunk costs emerge as the main success factors. Furthermore, the results of nonparametric tests are presented. They mostly confirm the econometric evidence. We also show that the quantitative results are consistent with the qualitative results of the surveys. Finally, we argue that the survey based approach to B2C eCommerce is a method that provides reliable and consistent data, and that it complements the approach based on prices and consumer behavior commonly applied.
Keywords: L10; L25; L81; L86; 330; B2C eCommerce; empirical evidence; success factors; endogenous sunk costs; Teleshopping; E-Business; Wettbewerbsstrategie; Marktstruktur; Sunk Costs; Erfolgsfaktor; Schätzung; Wien; Österreich